Ethynylation of Isoquinoline and Quinoline Derivatives with Calcium Carbide - Samzadeh-Kermani, Alireza (Synlett, 2017)
An operatically simple method for the ethynylation of isoquinolines and quinolines is described. The ionic adduct derived from an alkynoic ester and the N-heterocycle was attacked by calcium carbide to give the ethynylation product. The procedure uses tetrabutylammonium fluoride trihydrate as a catalyst in aqueous N,N-dimethylacetamide. Steric and electronic effects of various substituents on the outcome of the reaction were examined.
Keywords: ethynylation; isoquinolines; quinolines; calcium carbide; multicomponent reaction; alkynoic ester